Cardiovascular magnetic resonance evaluation of symptomatic severe aortic stenosis: association of circumferential myocardial strain and mortality. Issue 1 (December 2017) - Musa, Tarique; Uddin, Akhlaque; Swoboda, Peter; Fairbairn, Timothy; Dobson, Laura; Singh, Anvesha; Garg, Pankaj; Steadman, Christopher; Erhayiem, Bara; Kidambi, Ananth; Ripley, David; McDiarmid, Adam; et al.
Abstract Background It is unknown whether circumferential strain is associated with prognosis after treatment of aortic stenosis (AS). We aimed to characterise strain in severe AS, using myocardial tagging cardiovascular magnetic resonance (CMR), prior to and following Transcatheter Aortic Valve Implantation (TAVI) and Surgical Aortic Valve Replacement (SAVR), and determine whether abnormalities in strain were associated with outcome. Methods CMR was performed pre- and 6 m post-intervention in 98 patients (52 TAVI, 46 SAVR; 77 ± 8 years) with severe AS. TAVI patients were older (80.9 ± 6.4 vs. 73.0 ± 7.0 years, p < 0.01) with a higher STS score (2.06 ± 0.6 vs. 6.03 ± 3.4, p < 0.001). Tagged cine images were acquired at the basal, mid and apical LV levels with a complementary spatial modulation of magnetization (CSPAMM) pulse sequence. Circumferential strain, strain rate and rotation were calculated using inTag© software. Results No significant change in basal or mid LV circumferential strain, or of diastolic strain rate, was seen following either intervention. However, a significant and comparable decline in LV torsion and twist was observed (SAVR: torsion 14.08 ± 8.40 vs. 7.81 ± 4.51, p < 0.001, twist 16.17 ± 7.01 vs.12.45 ± 4.78, p < 0.01; TAVI: torsion 14.43 ± 4.66 vs. 11.20 ± 4.62, p < 0.001, twist 16.08 ± 5.36 vs. 12.36 ± 5.21, p < 0.001) which likely reflects an improvement towards normal physiology following relief of AS. Over a maximum 6.0y follow up, there were 23 (16%) deaths following valve intervention. On multivariable Cox analysis, baseline mid LV circumferential strain was significantly associated with all-cause mortality (hazard ratio, 1.03; 1.01–1.05; p = 0.009) independent of age, LV ejection fraction and STS mortality risk score. ROC analysis indicated a mid LV circumferential strain > −18.7% was associated with significantly reduced survival. Conclusion TAVI and SAVR procedures are associated with comparable declines in rotational LV mechanics at 6 m, with largely unchanged strain and strain rates. Pre-operative peak mid LV circumferential strain is associated with post-operative mortality.